Interação entre leitura e escrita : o impacto dos hábitos de leitura e da mediação em leitura na escrita de alunos do ensino médio - Silva, Geraldine Thomas da (2015)
This dissertation investigated the influence of the reading habit and of reading mediation in the production of argumentative texts by high school senior students, based especially in psycholinguistic postulates. The research sought to assess high school students production of argumentative texts, considering their reading habits (type and frequency of reading), as well as the fact of having been exposed or not to mediated reading by their teacher and colleagues. Data collection was performed with thirty senior students from a private high school in the Vale do Rio dos Sinos, in the Brazilian state of Rio Grande do Sul. Four phases integrated the experiment: the administration of a questionnaire on reading, a writing production (pre-test), reading mediation workshops and another writing production (post-test). Data were analyzed using a quantitative and qualitative. The results showed a significant variation among the group of students who have reading habit (G1) and the group who do not frequently read (G2). Therefore, it appears that frequent reading interferes with the performance of students in the production of argumentative texts. The writing improvement variation of the group of students exposed to the reading mediation workshop (G3 = formed by 7 of group 1 and 8 of group 2) at the pre-test (before the mediation) and post-test (after mediation) was not statistically significant. However, after mediation workshops, participants scores in writing were higher than those obtained in the pre-test, as showed by a qualitative analyses. Therefore, we observed that reading habits play a key role for the successful development of argumentative text production. As to the reading mediation effect, it seems to improve text production. However, its effect is lower than of reading habits in developing argumentative writing ability.